New Straits Times, 31 January 2009 (The New Straits Times Press (M) Bhd, 2009)
The US economy shrank at the fastest rate since Ronald Reagan's presidency, Japan's business outlook worsened, and European inflation tumblend, adding pressure on policymakers to quickly stimulate growth.